Immunoproteasome inhibition attenuates experimental psoriasis - del Rio Oliva, Marta; Mellett, Mark; Basler, Michael (Frontiers in Immunology, 2022)
Introduction Psoriasis is an autoimmune skin disease associated with multiple comorbidities. The immunoproteasome is a special form of the proteasome expressed in cells of hematopoietic origin. Methods The therapeutic use of ONX 0914, a selective inhibitor of the immunoproteasome, was investigated in Card14ΔE138+/- mice, which spontaneously develop psoriasis-like symptoms, and in the imiquimod murine model. Results In both models, treatment with ONX 0914 significantly reduced skin thickness, inflammation scores, and pathological lesions in the analyzed skin tissue. Furthermore, immunoproteasome inhibition normalized the expression of several pro-inflammatory genes in the ear and significantly reduced the inflammatory infiltrate, accompanied by a significant alteration in the αβ+ and γδ+ T cell subsets. Discussion ONX 0914 ameliorated psoriasis-like symptoms in two different murine psoriasis models, which supports the use of immunoproteasome inhibitors as a therapeutic treatment in psoriasis.